Pelatihan Manajemen Usaha Bagi Perempuan Pengusaha Mikro - Christine Marina Wakarmamu (Cenderabakti: Jurnal Pengabdian Kepada Masyarakat, 2023)
Community service activities in the form of business management training are carried out to increase the knowledge of micro-entrepreneurs in the Tanjung Ria Village who are working in the tourism sector, especially beach tourism. The problem faced so far is the difficulty of determining the right business idea, determining the selling price, and managing business finances. The methods used in this training are lectures, discussions, and exercises. This training provides benefits for micro-entrepreneurs in increasing their ability to determine the right business opportunities, setting competitive or competitive product selling prices, as well as increasing their ability to manage business finances.